Building Usability Knowledge for Health Information Technology: A Usability-Oriented Analysis of Incident Reports - Marcilly, Romaric; Schiro, Jessica; Beuscart-Zéphir, Marie Catherine; Magrabi, Farah (Applied Clinical Informatics, 2019)
Background The contribution of usability flaws to patient safety issues is acknowledged but not well-investigated. Free-text descriptions of incident reports may provide useful data to identify the connection between health information technology (HIT) usability flaws and patient safety.Objectives This article examines the feasibility of using incident reports about HIT to learn about the usability flaws that affect patient safety. We posed three questions: (1) To what extent can we gain knowledge about usability issues from incident reports? (2) What types of usability flaws, related usage problems, and negative outcomes are reported in incidents reports? (3) What are the reported usability issues that give rise to patient safety issues?Methods A sample of 359 reports from the U.S. Food and Drug Administration Manufacturer and User Facility Device Experience database was examined. Descriptions of usability flaws, usage problems, and negative outcomes were extracted and categorized. A supplementary analysis was performed on the incidents which contained the full chain going from a usability flaw up to a patient safety issue to identify the usability issues that gave rise to patient safety incidents.Results A total of 249 reports were included. We found that incident reports can provide knowledge about usability flaws, usage problems, and negative outcomes. Thirty-six incidents report how usability flaws affected patient safety (ranging from incidents without consequence, to death) involving electronic patient scales, imaging systems, and HIT for medication management. The most significant class of involved usability flaws is related to the reliability, the understandability, and the availability of the clinical information.Conclusion Incidents reports involving HIT are an exploitable source of information to learn about usability flaws and their effects on patient safety. Results can be used to convince all stakeholders involved in the HIT system lifecycle that usability should be considered seriously to prevent patient safety incidents.
Keywords: information technology; patient safety; ergonomics; databases, factual; software